2023
DOI: 10.1002/anie.202311140
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Ionic Fluids: Is There a Difference Between Chloride‐Based Brines and Deep Eutectic Solvents?

Guillaume Zante,
Christopher E. Elgar,
Katherine George
et al.

Abstract: Deep Eutectic Solvents (DESs) have been lauded as novel solvents, but is there really a difference between them and concentrated aqueous brines? They provide a method of adjusting the activity of water and chloride ions which can affect mass transport, speciation and reactivity. This study proposes a continuum of properties across concentrated ionic fluids and uses metal processing as an example. Charge transport is shown to be governed by fluidity and there is no discontinuity between molar conductivity and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In the case of precious metals, it has been reported that oxidative leaching in IL media improves the extraction of silver, while gold extraction was found similar to that achieved in the aqueous system. In DES media, it has been demonstrated that electrum, native Te, and tellurobismuthite are soluble by oxidation with iodine . This study shows very interesting results but lacks a comparison with the aqueous system and has been conducted only with very short leaching times.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of precious metals, it has been reported that oxidative leaching in IL media improves the extraction of silver, while gold extraction was found similar to that achieved in the aqueous system. In DES media, it has been demonstrated that electrum, native Te, and tellurobismuthite are soluble by oxidation with iodine . This study shows very interesting results but lacks a comparison with the aqueous system and has been conducted only with very short leaching times.…”
Section: Introductionmentioning
confidence: 99%